Preparation of metal hydroxide microcapsules and the effect on pH value of concrete. (30th November 2017) - Zuo, Jiandong; Zhan, Jia; Dong, Biqin; Luo, Chaoyun; Liu, Qiuhong; Chen, Dazhu
Highlights: Metal hydroxide microcapsules with sustained-release property were prepared. The release of microcapsules was mainly affected by the weight gain rate and polymer type of wall material. Microcapsules could effectively delay the decline on the pH values of concrete. Microcapsules could effectively decrease the corrosion rate of steel bar. Abstract: Polymer/metal hydroxide microcapsules with sustained-release property were prepared by centrifuge coating granulation method in order to stabilize pH value of concrete for protecting steel bar in concrete. Effects of microcapsules characteristics on the release rate of metal hydroxide in the solution simulating concrete pores were studied by thermo gravimetric analysis (TGA) and the stabilization effect of metal hydroxide microcapsules on the pH value of concrete were also discussed. The results revealed that the microcapsules with higher weight gain rate of wall material during fluidized bed coating processing had the slower release rate of core material. Moreover, the release rate of polymethyl methacrylate (PMMA) microcapsule was faster than that of ethyl cellulose (EC) microcapsule. Metal hydroxide microcapsules could delay the decline of pH value, especially PMMA microcapsules with 20% weight gain rate. In addition, metal hydroxide microcapsules could improve the pH values of actual concrete blocks and had better effect than those directly added in concrete. Surface corrosion morphology of steel bars immersed in the simulated solution showed that microcapsules could effectively retard the corrosion rate of steel bars, and the anticorrosion effect became better with the increase of microcapsules dosage.